Penerapan Algoritma Vegenere Cipher Dan Vernam Cipher Dalam Penggamanan File Text - Shabrizqi Zamara (JURIKOM (Jurnal Riset Komputer), 2019)
Kriftografi is one of the branches of subjects whose discussion is about security, data confidentiality and data integrity. But not all security can be solved by cryography. Cryptography can also be interpreted as science or art to maintain data security. When a data can be sent from one place to another, the contents of the data may be tapped by irresponsible parties. To maintain the data file, the data can be converted into a code that cannot be understood by other parties. Encryption is an encoding process that changes a code or data from what is commonly understood, called a plaintext, into a code that cannot be understood, called ciphertext. While the reverse process for converting a ciphertext into a plaintext is called decryption. The process of encryption and decryption requires a certain mechanism and key, and the unity of this system is often called a cipher. By using the classic vegenere cipher method and this cipher, it is expected to be able to secure text files. By encrypting and describing the text file, it becomes safer.